Breakage-fusion-bridge cycles leading to inv dup del occur in human cleavage stage embryos - Voet, Thierry; Vanneste, Evelyne; Van der Aa, Niels; Melotte, Cindy; Jackmaert, Sigrun; Vandendael, Tamara; Declercq, Matthias; Debrock, Sophie; Fryns, Jean-Pierre; Moreau, Yves; D'Hooghe, Thomas; Vermeesch, Joris R. (Human mutation, 2011)
Recently, a high incidence of chromosome instability (CIN) was reported in human cleavage stage embryos. Based on the copy number changes that were observed in the blastomeres it was hypothesized that chromosome breakages and fusions occur frequently in cleavage stage human embryos and instigate subsequent breakage‐fusion‐bridge cycles. In addition, it was hypothesized that the DNA breaks present in spermatozoa could trigger this CIN. To test these hypotheses, we genotyped both parents as well as 93 blastomeres from 24 IVF embryos and developed a novel single nucleotide polymorphism (SNP) array‐based algorithm to determine the parental origin of (aberrant) loci in single cells. Paternal as well as maternal alleles were commonly rearranged in the blastomeres indicating that sperm‐specific DNA breaks do not explain the majority of these structural variants. The parent‐of‐origin analyses together with microarray‐guided FISH analyses demonstrate the presence of inv dup del chromosomes as well as more complex rearrangements. These data provide unequivocal evidence for breakage–fusion–bridge cycles in those embryos and suggest that the human cleavage stage embryo is a major source of chromosomal disorders. Hum Mutat 32:783–793, 2011. © 2011 Wiley‐Liss, Inc.